2017
DOI: 10.4025/actascianimsci.v39i1.33085
|View full text |Cite
|
Sign up to set email alerts
|

<b>Grazing behavior and spatial distribution of feces of Young bulls in silvopastoral systems and Marandu monoculture in the Pre-Amazon region

Abstract: ABSTRACT.The objective was to evaluate the grazing behavior and the spatial distribution of feces of F1 young bulls from the cross between Nellore and Guzera on pastures of Urochloa brizantha cv. Marandu in silvopastoral systems composed of babassu palm (Attalea speciosa) and Marandu monoculture in the Pre-Amazon region of the state of Maranhão. Animals were evaluated in four systems consisting of 0, 80, 131, 160 palms ha -1 , characterizing monoculture (mono), low density of palm trees (LD), medium density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This observation is probably a consequence of the positive effect of the tree shading on grazing activity. At 7:00h, shading caused better thermal comfort by limiting direct exposure to solar radiation thereby enabling the heifers to spend more time grazing (Araújo et al, 2017). The greater grazing time spent at 22:00h in the ICLF system could be as a result of the greater time spent in rumination at 18:00h (Figure 4), which permitted the heifers to empty their rumen and return to grazing activity at 22:00h.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is probably a consequence of the positive effect of the tree shading on grazing activity. At 7:00h, shading caused better thermal comfort by limiting direct exposure to solar radiation thereby enabling the heifers to spend more time grazing (Araújo et al, 2017). The greater grazing time spent at 22:00h in the ICLF system could be as a result of the greater time spent in rumination at 18:00h (Figure 4), which permitted the heifers to empty their rumen and return to grazing activity at 22:00h.…”
Section: Resultsmentioning
confidence: 99%
“…Pastures are the basis for sustaining livestock activity in tropical regions. Despite the low cost of grazing production, this is strongly affected by the statehood of production, which limits the performance of herds in certain periods of the year, such as in the semiarid region of northeastern Brazil (ARAÚJO et al, 2017). In these regions, the maximum forage production, both in quantity and quality, occurs during the period in which the highest rainfall indices are concentrated, being reduced in the dry season, mainly due to drought (MARANHÃO et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that such changes interfere with the sward structure and, consequently, with the grazing behavior of the animals. Araújo et al (2017) reported that in systems with higher densities of babassu palms there was grass etiolation and the movement of the animals along the paddock varied according to sward height.…”
Section: Discussionmentioning
confidence: 99%